Android-Based E-Voting Application Using Universally Unique Identifier (uuid) Governor Election Bem Faculty of Engineering (case Study: Bhayangkara University Surabaya) - Muhammad Ramadhan Dwiki Asmaradani; Arif Arizal; Rani Purbaningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Election of the Governor and Deputy Governor of the Student Executive Board of the Faculty of Engineering(BEM FT) Bhayangkara University Surabaya is an activity where each student uses his voting rights. Theselection is done by voting with the candidate who has the most votes coming out as winners. The selection of theGovernor of UB's FT BEM is still not maximally indicated by the voter data, which is still small compared to thenumber of active students. Procedures that are still conventional with students having to go to campus to votecan be the cause. Therefore, the use of information and communication technology gave rise to the idea ofmaking an electronic voting system or commonly called Android-based E-Voting using the Universally UniqueIdentifier (UUID). E-Voting is a method of voting and vote counting in an election using a mobile phoneelectronic device. In other words, this technology makes it easy for voters in a general election to exercise theirvoting rights by using electronic and internet media. With the E-Voting, it is expected that the interest of studentsto participate in giving more votes and the sound processing process will be faster.